The Implementation of Project Based Learning in the Concrete Practice Course - Zaus, Anggun Agni; Syah, Nurhasan (Universitas Negeri Padang, 2023)
A learning model that can be implemented in the Stone and Concrete Practice course is the Project Based Learning (PjBL) model, which emphasizes project-based learning. The objective of this research is to provide a description of the implementation of project-based learning in the stone and concrete practice courses. This study employs a Pre-Experimental Design utilizing a One-Shot Case Study design. The instrument utilized in this research is the assessment of skills in Project Based Learning. From the results of the study it can be interpreted that the application of Project Based Learning in the Stone and Concrete Practice course obtains the proportion of Respondent Achievement Level (TCR) of the six assessment components of 83.85% which belongs to the good category. Consequently, the application of the Project Based Learning learning model in the Stone and Concrete Practice course leads to an improvement in students' masonry and concrete work skills.